Unemployed and disabled for work: identifying 3-year labour market pathways from the beginning of a sickness absence using sequence and cluster analyses in a register-based longitudinal study in Finland - Mikko Laaksonen; Jenni Blomgren; Riku Perhoniemi (BMJ Open, 2023)
Objectives This study followed the labour market pathways of unemployed persons who started a sickness absence (SA) spell. We aimed to unravel subgroups based on altering labour market states and to identify covariates of these subgroups.Design Register-based longitudinal study, with nine labour market states and 36-month units.Setting and participants All Finnish persons aged 18–59 years with an SA in 2016 who were unemployed at the start of the SA spell (N=12 639).Outcome measures Sequence analysis was used to study transitions between nine labour market states based on monthly register data on permanent and temporary (full and partial) disability pensions (DP), rehabilitation, all-cause SA, unemployment and employment. Individuals were grouped into clusters based on cluster analysis and intersequence distances. Multinomial regression analysis was used to examine covariates of cluster memberships.Results Six clusters with the following pathway identities were found: (1) recurring unemployment (44%); (2) employment after a short SA (18%); (3) rehabilitation, recurring SA and unemployment (12%); (4) unknown sources of income (11%); (5) permanent DP after a prolonged SA (9%) and (6) temporary DP after a prolonged SA (7%).Compared with the reference cluster 2, all other clusters were associated with less employment days and having a chronic illness before the SA spell, SA based on a mental disorder and a rejected DP application during the follow-up. In addition, the clusters had some unique covariates.Conclusions Unemployed persons starting an SA are a heterogeneous group, with different labour market pathways. For many, the combination of unemployment and work disability means low chances for employment or regained work ability during the following years. Unemployed persons with poorer health, long history outside employment, older age, low educational level, a rejected DP application and a mental disorder could benefit from targeted support.